2004
DOI: 10.1152/ajplung.00160.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prostasin, a membrane-anchored serine peptidase, regulates sodium currents in JME/CF15 cells, a cystic fibrosis airway epithelial cell line

Abstract: . Prostasin, a membrane-anchored serine peptidase, regulates sodium currents in JME/CF15 cells, a cystic fibrosis airway epithelial cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 37 publications
(32 reference statements)
2
57
0
1
Order By: Relevance
“…1A, prostasin migrates as 37-and 40-kDa bands in the apical secretions; however, no prostasin was observed in the basolateral secretions. These results are consistent with previous reports of prostasin secretion from human prostate tissue (48) and from various immortalized mouse cell lines (36,45) but differ from a study in the immortalized bronchial epithelial cell line JME/CF15, in which prostasin was not present in the secretions (43). To clarify whether prostasin is secreted in the airway, we also performed Western blotting on sputum from a CF patient (Fig.…”
Section: Prostasin Is Expressed In a Nonpolarized Distribution But Onsupporting
confidence: 91%
See 1 more Smart Citation
“…1A, prostasin migrates as 37-and 40-kDa bands in the apical secretions; however, no prostasin was observed in the basolateral secretions. These results are consistent with previous reports of prostasin secretion from human prostate tissue (48) and from various immortalized mouse cell lines (36,45) but differ from a study in the immortalized bronchial epithelial cell line JME/CF15, in which prostasin was not present in the secretions (43). To clarify whether prostasin is secreted in the airway, we also performed Western blotting on sputum from a CF patient (Fig.…”
Section: Prostasin Is Expressed In a Nonpolarized Distribution But Onsupporting
confidence: 91%
“…Donaldson et al (13) demonstrated that prostasin is expressed in airway epithelium and increases the Na ϩ current by ϳ75% when coexpressed with ENaC in Xenopus oocytes. Furthermore, Tong et al (43) reported an ϳ75% reduction in the Na ϩ conductance of an immortalized airway epithelial cell line following small interference (si)RNAmediated prostasin knockdown. Recent evidence from Bruns et al (4) demonstrated that prostasin cleaves the extracellular loop of the ␥ENaC subunit and thereby increases the open probability of the channel.…”
mentioning
confidence: 99%
“…The physiological function of Testisin is still not clear. In the case of prostasin, one role that has been identified is the regulation of epithelial Na þ channel (ENaC) function that is critical for normal salt and water balance (Vuagniaux et al, 2000;Tong et al, 2004).…”
mentioning
confidence: 99%
“…In addition, the serine protease inhibitor aprotinin reduces the transepithelial sodium transport in an amphibian kidney cell line. In airway epithelial cell lines, elastase, another serine protease, activates ENaC, and a decrease in the expression of prostasin reduces the amiloride-sensitive Na ϩ current (70,71). Clearly, the Po of ENaC is increased by extracellular proteases, an effect on the channel that is independent of changes in intracellular Ca 2ϩ or activation of G protein-coupled receptors (72,73).…”
Section: Modulatory Sites Of Enac Activitymentioning
confidence: 99%